2010
DOI: 10.1123/jpah.7.s2.s196
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Built Environment Associated With Leisure-Time Physical Activity Among Adults in Bogotá, Colombia: A Multilevel Study

Abstract: Background:Even though there is increasing evidence that the built environment (BE) has an influence on leisure-time physical activity (LTPA), little is known about this relationship in developing countries. The objective of this study was to assess the associations between objective built environment characteristics and LTPA.Methods:A cross-sectional multilevel study was conducted in 27 neighborhoods in which 1315 adults aged 18−65 years were surveyed. An adapted version of the IPAQ (long version) was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 21 publications
4
53
0
15
Order By: Relevance
“…85 Low-income populations are financially constrained in choosing activity-friendly alternatives such as living in a safer neighborhood, purchasing a gym membership, paying a fee to access a recreation center, or procuring services that afford time for PA such as housecleaning or childcare. 86,87 Overall, these variations in leisure and travel PA are consistent with previous research in LMICs such as Nigeria, 70 Brazil, 71,[88][89][90] Columbia, 83,91,92 Bangladesh, 60,93 and Sri Lanka. 94 A comparison of travel PA between the high-SES neighborhoods showed that a higher percentage of residents in the low walkability neighborhoods reported meeting travel PA recommendations compared to high walkability neighborhoods, which is a counter-intuitive finding.…”
Section: Discussionsupporting
confidence: 89%
“…85 Low-income populations are financially constrained in choosing activity-friendly alternatives such as living in a safer neighborhood, purchasing a gym membership, paying a fee to access a recreation center, or procuring services that afford time for PA such as housecleaning or childcare. 86,87 Overall, these variations in leisure and travel PA are consistent with previous research in LMICs such as Nigeria, 70 Brazil, 71,[88][89][90] Columbia, 83,91,92 Bangladesh, 60,93 and Sri Lanka. 94 A comparison of travel PA between the high-SES neighborhoods showed that a higher percentage of residents in the low walkability neighborhoods reported meeting travel PA recommendations compared to high walkability neighborhoods, which is a counter-intuitive finding.…”
Section: Discussionsupporting
confidence: 89%
“…It is located at 2,630 m above sea level, has an average temperature of 14°C, no seasons, and an estimated 7 million residents. In 2000, the Human Development Index (HDI) for these residents was 0.81, the GINI index (a measure of inequality that varies between 0-complete equality and 1-complete inequality) was 0.57, and the city had 4.12 m 2 of green area per inhabitant [26]. The current literacy rate is 96% with 18% of the residents having completed high school and 22% having more than a high-school education.…”
Section: Definitionsmentioning
confidence: 99%
“…7,8 In some countries, access to activity-supportive environments varied significantly by neighborhood disadvantage. [17][18][19] Most studies of built environments have been conducted in the USA, Australia and Western Europe, with recent studies extending findings to Japan, 20 Colombia, 21 and Brazil. [22][23][24] Though the results have been mostly consistent, common methods were not employed, self-report measures of physical activity and environmental attributes dominated, and the limited variability in environmental exposures and physical activity within countries may have underestimated the strength of association.…”
mentioning
confidence: 99%